Peran Literasi Lingkungan dalam Pendidikan Sekolah Menengah: Analisis Literatur - Kharisma Sinta Saputri; Sukarmin Sukarmin; Sarwanto Sarwanto (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The rapid environmental changes caused by human activities have become a pressing global issue. Problems such as climate crises, pollution, loss of biodiversity, and other environmental damage require serious attention from all sectors. This study aims to analyze environmental literacy in high schools through a literature review focused on the concept and challenges of its implementation. The study uses a literature review approach to analyze the role of environmental literacy in high school education. This approach was chosen to provide an in-depth understanding of previous research findings related to environmental literacy. Through this literature review, the research can identify trends, challenges, and gaps in the teaching of environmental literacy in high schools. Environmental literacy is defined as students' ability to understand and apply basic environmental concepts and make wise decisions in maintaining environmental sustainability. However, its implementation in high schools still faces many obstacles, such as a lack of practical education, theoretical learning approaches, and low student interest and concern for environmental issues. This study uses a literature review approach to identify trends, gaps, and challenges in the teaching of environmental literacy, as well as provide recommendations to improve the effectiveness of environmental education in high schools. The results are expected to contribute to global efforts in mitigating environmental problems through education.